Ion channels in k562 human leukemic cells and the relation with the multidrug resistance - Assef, Yanina (2008)
Enhanced proliferation, aberrant differentiation, and impaired ability to die are the prime reasons for abnormal tissue growth, which can eventually turn into uncontrolled expansion and invasion, characteristic of cancer. Ion channels contribute to virtually all basic cellular processes, including those for maintaining tissue homeostasis as proliferation, differentiation, and apoptosis (1). Changes in cell volume are crucial events during both cell proliferation and apoptosis and thus on tumor development and growth (2). Cell proliferation depends on an increased cell volume and cell shrinkage is a characteristic of apoptosis. Potassium, calcium, chloride channels and others are abnormally expressed in the membrane of tumor cells. By the regulation of membrane voltage, cell volume, Ca2+ signaling, cytosolic pH and cell cycle, they can adjust the cell proliferation and apoptosis. The specific blockade of ion channels may not only allow the dissection of the channel role in distinct physiologic processes, but because of the implication of them in tumor development, it may also offer an opportunity for the treatment of cancer. However, many ion channels are structurally similar to one another, and it has been notoriously difficult to obtain specific blockers for any given channel, thus it is essential to generate more potent and specific inhibitors of ion channels before using them in human therapeutics.